Growing and development of sunflower hybrids depending on plant density standing - Маслійов, С. В.; Степанов, В. В.; Калініченко, М. В.; Ярчук, І. І. (Scientific Progress & Innovations, 2018)
A significant place in solving the problem of increasing the yield of sunflower is taken by the improvement of the varietal agrotechnology of sunflower cultivation. The best technology of growing sunflower hybrids to obtain a high yield is described. In conditions of Luhansk region the best sunflower precursors are winter crops, corn, legumes, barley. In our case, winter wheat was a precursor of the sunflower. Recommendations for the soil treatment, application of mineral fertilizers, sowing time, seeding rates, and crop care were provided. In autumn, plowing to a depth of 25-27 cm was carried out. In the spring, in order to close the humidity by plowing, an alignment of the plow land was carried out. Due to the weak clogging with weeds, one pre-sowing cultivation was carried out to a depth of 5-6 cm. Herbicide was introduced directly before cultivation against the weeds. Hybrids resistant to: phomopsis, white rot of composite flowers, white rot of stems and downy mildew are recommended. Experiments were carried out on changing the width of the rows between the sunflower hybrids from 70 cm to 15 cm. Every varieties of plant standing were presented to each variant of sowing; 70; 60; 50; 40 th/h. The studies were conducted on experimental plots of the Department of Biology and Agronomy of Taras Shevchenko. Luhansk National University. In experiments, hybrids of domestic breeding Jason, Hector, Basalt, Suchasnyk were planted; these hybrids cover the main morphotypes and groups of ripeness, which are most common in collective farms. The results showed that the methods of sowing influenced the quality of the seeds, but in most years there has been an increase in oil content on continuous sowing. The thickening of sunflower promotes an increase in oil content and a decrease in the protein content of seeds. The best seed quality was the Basalt hybrid.